2018
DOI: 10.1103/physrevlett.120.190401
|View full text |Cite
|
Sign up to set email alerts
|

Causal Modeling the Delayed-Choice Experiment

Abstract: Wave-particle duality has become one of the flagships of quantum mechanics. This counterintuitive concept is highlighted in a delayed-choice experiment, where the experimental setup that reveals either the particle or wave nature of a quantum system is decided after the system has entered the apparatus. Here we consider delayed-choice experiments from the perspective of device-independent causal models and show their equivalence to a prepare-and-measure scenario. Within this framework, we consider Wheeler's or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 22 publications
5
61
0
Order By: Relevance
“…A delayed choice experiment as a prepare and measure scenario -As recently noted in [21], a DCE ( Fig. 2b) can be seen as a particular instance of a PAM scenario ( Fig.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…A delayed choice experiment as a prepare and measure scenario -As recently noted in [21], a DCE ( Fig. 2b) can be seen as a particular instance of a PAM scenario ( Fig.…”
mentioning
confidence: 81%
“…In spite of the fact that Wheeler's and quantum DCEs are of classical nature from the DI perspective, it has also been shown that minor modifications of the original proposals can rule out, with a DI protocol, HV models as a possible explanation [21]. In this new framework, apart from the assumption of non-retrocausality, the HV is also assumed to have the same dimension as the quantum system it is supposed to mimic.…”
mentioning
confidence: 99%
“…Recently, a new proposal [19] based on the causal model demonstrated that a two-dimensional classical hidden variable model could explain the outcomes of WDCE and QDCE. Herein, the delayed-choice experiments could be considered from the perspective of deviceindependent causal models in a prepare-and-measure scenario.…”
mentioning
confidence: 99%
“…In Ref. [19], Chaves et al proposed that the delayed-choice experiment can be regarded as a DI prepare-and-measure (PAM) scenario ( Fig. 1(b)).…”
mentioning
confidence: 99%
“…Again, the quantum properties are not determined until the full system, comprising both photons in an entangled state, has been measured. Since their early conception [7,3], "delayed-choice" techniques have been extended to scenarios beyond the wave-particle duality [8,4] and continue to attract the interest of researchers to this date [9].…”
mentioning
confidence: 99%